Saturable reactor hysteresis model based on Jiles–Atherton formulation for ferroresonance studies. (October 2018) - Sima, Wenxia; Zou, Mi; Yang, Ming; Peng, Daixiao; Liu, Yonglai
Highlights: A novel ψ – i JA hysteresis reactor is proposed. The potential difference of the reactor is used to calculate the dynamic losses. The asymmetric minor hysteresis loops can be obtained in ferroresonance simulations. The proposed reactor is verified by ferroresonance experiments. Abstract: Despite remarkable achievements in the field of Jiles–Atherton (JA) hysteresis theory, JA hysteresis modeling remains challenging given that most commercial software still lacks a practical dynamic JA hysteresis reactor model for electromagnetic transients. A novel voltage-driven dynamic flux linkage–current ( ψ–i ) JA hysteresis reactor in Electromagnetic Transients Program–Alternative Transients Program (EMTP–ATP) is developed in this study. The proposed model is based on flux linkage and current instead of magnetic flux density and magnetic field. Voltage-driven dynamic losses are incorporated into the static ψ–i JA hysteresis model by using Type-94 element in EMTP–ATP. The two proposed models in this paper are validated using current tests under 50 and 150 Hz. The performance of the proposed dynamic Model 1 matches better with experiments than the dynamic Model 2. Ferroresonance tests are carried out to validate the performance of the proposed reactor. The results show that the proposed reactor has a broad application prospect in electromagnetic transient studies.